Tolterodine ER reduced increased bladder wall thickness in women with overactive bladder. A randomized, placebo‐controlled, double‐blind, parallel group study. Issue 1 (13th April 2017) - Bray, Rhiannon; Cartwright, Rufus; Cardozo, Linda; Hill, Simon; Guan, Zhonghong; Khullar, Vik
Abstract : Aims: We evaluated the effect of Tolterodine extended release (TER) versus placebo on bladder wall thickness (BWT) using transvaginal ultrasound in women with overactive bladder (OAB). Materials and Methods: We recruited 79 women with symptoms of OAB with a mean age of 47 years who had a BWT of at least 5 mm and a post‐micturition volume of less than 50 mL at screening. Subjects received TER 4 mg or placebo once daily for the first 12 weeks of the study. For the subsequent 12 weeks, all subjects received TER 4 mg once daily. BWT was measured at screening, weeks 12 and 24. Subjects recorded number of micturitions, incontinence episodes and urgency episodes, and volume voided per micturition at regular intervals during the study. Results: Treatment with TER for 12 weeks produced a statistically significant decrease from baseline in BWT (mean [SD] = 0.9 [1.4] mm; P < 0.05) that was not evident following treatment with placebo (0.2 [1.6] mm; P = 0.54). However, the treatment difference did not reach statistical significance (LS Mean = −0.4; 95%CI: −1.2, 0.3; P = 0.25). After 12 weeks of treatment, subjects who had taken TER showed an improvement in each bladder diary variable compared to placebo‐treated subjects. Conclusions: TER may have a direct effect on BWT in women with OAB. Larger studies are warranted to further investigate the effect of behavioral interventions and antimuscarinics, such as TER, on BWT in women with OAB and increased BWT.